The Effect of Color and Photoperiod on Body Coloration and Growth of Juvenile Redclaw Crayfish (Cherax quadricarinatus) - Muhammad Ibnu Sina; Syukriah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to determine the effects of light color and photoperiod on body coloration and growth performance of juvenile redclaw crayfish (Cherax quadricarinatus). A total of 144 juvenile crayfish were used in an experimental design consisting of six treatments based on two light colors (red and white LEDs) and three photoperiod regimes (6, 12, and 18 hours). The observed parameters included growth performance, survival rate, and changes in body coloration. The results showed that (1) red LED treatment with a 6-hour photoperiod produced the most optimal growth, whereas the 18-hour photoperiod treatment induced stress that led to reduced growth performance; (2) red LED treatments resulted in higher survival rates compared to white LED treatments; and (3) photoperiod significantly influenced changes in body coloration, with juveniles exhibiting blue and brown pigmentation. In conclusion, photoperiod affects affected the growth of juvenile crayfish, with red LED exposure for 6 hours representing representing the optimal condition. Differences in light color contribute to improved survival rates contributed to higher survival rates, while photoperiod plays a role in influencing body color changes played an important role in influencing changes in body coloration.